Methylammonium-free, high-efficiency, and stable all-perovskite tandem solar cells enabled by multifunctional rubidium acetate - Xufeng Liao; Xuefei Jia; Weisheng Li; Xiting Lang; Jianhua Zhang; Xinyu Zhao; Yitong Ji; Qingguo Du; Chun-Hsiao Kuan; Zhiwei Ren; Wenchao Huang; Yang Bai; et al. (Nature Communications)
Abstract All-perovskite tandem solar cells (APTSCs) offer the potential to surpass the Shockley-Queisser limit of single-junction solar cells at low cost. However, high-performance APTSCs contain unstable methylammonium (MA) cation in the tin-lead (Sn-Pb) narrow bandgap subcells. Currently, MA-free Sn-Pb perovskite solar cells (PSCs) show lower performance compared with their MA-containing counterparts. This is due to the high trap density associated with Sn2+ oxidation, which is exacerbated by the rapid crystallization of MA-free Sn-containing perovskite. Here, a multifunctional additive rubidium acetate (RbAC) is proposed to passivate Sn-Pb perovskite. We find that RbAC can suppress Sn2+ oxidation, alleviate microstrain, and improve the crystallinity of the MA-free Sn-Pb perovskite. Consequently, the resultant Sn-Pb PSCs achieve a power conversion efficiency (PCE) of 23.02%, with an open circuit voltage (Voc) of 0.897 V, and a filling factor (FF) of 80.64%, and more importantly the stability of the device is significantly improved. When further integrated with a 1.79-electron volt MA-free wide-bandgap PSC, a 29.33% (certified 28.11%) efficient MA-free APTSCs with a high Voc of 2.22 volts is achieved.